Massive stars unveil the origin of the giant gas ring in Leo - Corbelli, Edvige (Il Colle di Galileo, 2021)
The origin of the most extended intergalactic cloud of the local Universe, the Leo ring, has been debated for about 40 years. It has a gas mass equivalent to that of a galaxy but no extended optical counterpart. Recent observations with integral field spectroscopy have localized small star formation sites with young, massive stars in the cloud. The light from the hot gas in their proximity has the footprints of heavy elements with abundances close to solar ones, unveiling the long-standing mystery of the origin of this giant ring.